Peningkatan Pembelajaran Materi Perubahan Wujud Benda melalui Model Pembelajaran Project Based Learning Bagi Anak Autis - Putri, Wike Widya; Nurhastuti, Nurhastuti; Agusta, Rini (Jurnal Penelitian Pendidikan Khusus, 2023)
This research is motivated by the problems found in SLB Negeri 1 Padang in class VII Autism, the low learning outcomes in material changes in the form of objects. At the time of learning the teacher uses methods and lectures, exercises and questions and answers. This study aims to improve the process and learning outcomes of material changes in the form of objects through a project based learning model. The research method used was classroom action research consisting of two cycles. Based on the results of the research, the learning outcomes of material changes in the shape of objects increased compared to before using the project based learning model. This can be seen from the learning process and student learning outcomes which increase in each cycle